Temperature-compensated aluminum nitride lamb wave resonators - Lin, Chih-Ming (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2010)
In this paper, the temperature compensation of AlN Lamb wave resonators using edge-type reflectors is theoretically studied and experimentally demonstrated. By adding a compensating layer of SiO2 with an appropriate thickness, a Lamb wave resonator based on a stack of AlN and SiO2 layers can achieve a zero first-order temperature coefficient of frequency (TCF). Using a composite membrane consisting of 1 microm AlN and 0.83 microm SiO2, a Lamb wave resonator operating at 711 MHz exhibits a first-order TCF of -0.31 ppm/degrees C and a second-order TCF of -22.3 ppb/degrees C(2) at room temperature. The temperature-dependent fractional frequency variation is less than 250 ppm over a wide temperature range from -55 degrees C to 125 degrees C. This temperature-compensated AlN Lamb wave resonator is promising for future applications including thermally stable oscillators, filters, and sensors